Immunogenicity of GamLPV, an intranasal live vaccine for pertussis prevention, in adult volunteers: a blind, randomised, placebo-controlled trial to optimise the method and schedule of administration - A. A. Lidzhieva; A. Yu. Medkova; S. V. Kulikov; L. N. Sinyashina; R. A. Sioundioukova; I. N. Chernyshova; M. V. Gavrilova; K. K. Bushkova; N. A. Snegireva; I. N. Dyakov; G. I. Karataev (Биопрепараты: Профилактика, диагностика, лечение, 2025)
INTRODUCTION. Currently used inactivated vaccines with acellular/whole-cell pertussis components do not provide sterilising or sufficiently long-lasting immunity, nor do these vaccines prevent the spread of the pathogen or infection. A live pertussis vaccine for intranasal administration, GamLPV, has passed the necessary preclinical studies and a clinical trial that established the optimal dose for single-dose vaccination.AIM. This study aimed to optimise the method and schedule of administration of the GamLPV intranasal live vaccine for pertussis prevention on the basis of the immunogenicity results obtained in a clinical trial involving healthy volunteers aged 18 to 40 years.MATERIALS AND METHODS. This blind, randomised, placebo-controlled clinical trial enrolled 50 healthy adults, who were then randomised into two groups according to the method of GamLPV administration (drops or spray). The study evaluated the efficacy of two administration schedules, including single-dose vaccination and double-dose vaccination with an interval of 60 days. The study analysed nasopharyngeal and oropharyngeal aspirates, serum samples, and peripheral blood mononuclear cells from volunteers. The levels of IgM, IgA, and IgG antibodies specific to Bordetella pertussis and the levels of secretory IgA antibodies were measured in serum samples and nasal aspirates, respectively, by enzyme-linked immunosorbent assay. Agglutinating antibody titres were determined by agglutination tests. The quantitative determination of B. pertussis DNA in aspirates used real-time polymerase chain reaction. Cell-mediated immune responses were assessed by the production of IFN-γ and IL-17 cytokines in peripheral blood mononuclear cells.RESULTS. GamLPV administration to volunteers induced B. pertussis-specific IgG and IgA antibodies observed in serum samples, secretory IgA antibodies identified in aspirates, and increased titres of total antibodies to B. pertussis measured by agglutination tests, regardless of the vaccination schedule and the method of administration. Repeated GamLPV administration had a pronounced booster effect, as evidenced by elevated titres of antibodies of all classes from day 14. Moreover, repeated vaccination reduced the time for clearance of B. pertussis bacteria compared with that after the first vaccination (from 28 to 14 days). There were no significant differences in the time courses and values of the measured parameters for nasal vaccine delivery by spray and drops.CONCLUSIONS. Intranasal vaccination with GamLPV induces pronounced humoral and cellular immune responses and nasal mucosal immunity against pertussis infection in adults. The recommended method for GamLPV administration is nasal drops. The accelerated clearance of bacteria observed after the second vaccination is indicative of sterilising immunity provided by the first vaccination, which can ultimately reduce pertussis transmission in the population.